NAT10/ac 4 C drives intrahepatic cholangiocarcinoma by suppressing transposable elements via chromatin remodeling - Yunkun Lu; Kainan Lin; Qianqian Wang; Xiang Huang; Lianyu Lin; Jie Dou; Yajuan Jiao; Yali Wang; Peng Xiao; Hongjun Chen; Silin Li; Yangtao Xue; et al. (Proceedings of the National Academy of Sciences, 2026)
Intrahepatic cholangiocarcinoma (ICC) poses a significant clinical challenge due to its insidious onset, aggressive biological behavior, and propensity for early metastasis, contributing to a dismal 5-y survival rate of less than 10%. Despite advances in understanding the dynamic changes in gene regulatory networks and chromatin landscapes during tumorigenesis, the functional interplay between RNA epitranscriptomic modifications and nuclear events in ICC remains poorly elucidated. Here, we identify N -acetyltransferase 10 (NAT10), the writer for N 4 -acetylcytidine (ac 4 C) mRNA modification, as a critical regulator of ICC malignancy. Integrated multiomics profiling reveals that NAT10-mediated ac 4 C modification enhances the mRNA stability of chromatin assembly factor 1 subunit A (CHAF1A), a key chromatin regulator. Mechanistically, the NAT10–ac 4 C–CHAF1A axis robustly and epigenetically suppresses the expression of the nuclear transposable element HERV9NC, leading to diminished double-stranded RNA accumulation. This epigenetic silencing not only fuels ICC proliferation and migration but also attenuates intrinsic innate immune responses, thereby fostering an immunosuppressive tumor microenvironment characterized by reduced cytotoxic T cell infiltration and impaired tumor surveillance. Pharmacological inhibition of NAT10 with small-molecule compounds demonstrated robust therapeutic efficacy in both patient-derived xenograft and orthotopic tumor transplantation models of ICC. Collectively, our study unveils NAT10 as a master integrator of RNA epitranscriptomic reprogramming and nuclear chromatin dynamics in ICC, providing interesting mechanistic insights into the molecular basis of ICC progression. We also establish NAT10-ac 4 C modification as a druggable vulnerability, offering a promising therapeutic strategy for this aggressive malignancy.